Synthesis of arylamino-thieno-oxobutanamides and reactivity studies on the cyclisation with the Lawesson´s reagent - Raposo, M. Manuela M. (2004)
1-aryl-2-thienyl-substituted pyrroles and 5-arylamino-2,2´-bithiophenes are synthesized by treatment of arylamino-thieno-oxobutanamides with Lawesson´s reagent. These in turn are prepared by direct amidation of 4-oxo-(2-thienyl)butanoic acid through DCC/BtOH mediated reaction.